Molecular characterization of 22 novel UDP-N-acetylglucosamine-1-phosphate transferase α- and β-subunit (GNPTAB) gene mutations causing mucolipidosis types IIα/β and IIIα/β in 46 patients - Tappino, Barbara; Chuzhanova, Nadia A; Regis, Stefano; Dardis, Andrea; Corsolini, Fabio; Stroppiano, Marina; Tonoli, Emmanuel; Beccari, Tommaso; Rosano, Camillo; Mucha, Jan; Blanco, Mariana; Szlago, Marina; et al. (Human mutation, 2009)
Mutational analysis of the GNPTAB gene was performed in 46 apparently unrelated patients with mucolipidosis IIα/β or IIIα/β, characterized by the mistargeting of multiple lysosomal enzymes as a consequence of a UDP-GlcNAc-1-phosphotransferase defect. The GNPTAB mutational spectrum comprised 25 distinct mutant alleles, 22 of which were novel, including 3 nonsense mutations (p.Q314X, p.R375X, p.Q507X), 5 missense mutations (p.I403T, p.C442Y, p.C461G, p.Q926P, p.L1001P), 6 microduplications (c.749dupA, c.857dupA, c.1191_1194dupGCTG, c.1206dupT, c.1331dupG, c.2220_2221dupGA) and 8 microdeletions (c.755_759delCCTCT, c.1399delG, c.1959_1962delTAGT, c.1965delC, c.2550_2554delGAAAA, c.3443_3446delTTTG, c.3487_3490delACAG, c.3523_3529delATGTTCC). All micro-duplications/deletions were predicted to result in the premature termination of translation. A novel exonic SNP (c.303G>A; E101E) was identified which is predicted to create an SFRS1 (SF2/ASF) binding site that may be of potential functional/clinical relevance. This study of mutations in the GNPTAB gene, the largest yet reported, extends our knowledge of the mutational heterogeneity evident in MLIIα/β/MLIIIα/β.